2012
DOI: 10.3920/bm2011.0046
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the murine microbiome with a concomitant anti-obesity effect by Lactobacillus rhamnosus GG and Lactobacillus sakei NR28

Abstract: The microbiota of the gastrointestinal tract (GIT) constitutes the major part of the total human microbiome and is considered to be an important regulator of human health and host metabolism. Numerous investigations in recent years have focused on the connection between the human microbiota and metabolic diseases such as obesity, type II diabetes and atherosclerosis. Yet, little is known about the impact of probiotic consumption on the GIT microbial population and the potential effect on chronic diseases. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 47 publications
(48 reference statements)
6
53
0
Order By: Relevance
“…Numerous studies have provided evidence that kimchi contains many beneficial probiotics, including that from LAB species. [43][44][45][46][47] In accordance with this, L. plantarum LG42 isolated from gajami-sikhae showed probiotic effects including anti-obesity properties. 7,11) A strain of L. sakei isolated from another food had been evaluated for its probiotic potential such as gastric resistance, survival, and bacteriocin production in the presence of bile salts and commercial prebiotics, and reducing the adhesion of Listeria monocytogenes to intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 68%
“…Numerous studies have provided evidence that kimchi contains many beneficial probiotics, including that from LAB species. [43][44][45][46][47] In accordance with this, L. plantarum LG42 isolated from gajami-sikhae showed probiotic effects including anti-obesity properties. 7,11) A strain of L. sakei isolated from another food had been evaluated for its probiotic potential such as gastric resistance, survival, and bacteriocin production in the presence of bile salts and commercial prebiotics, and reducing the adhesion of Listeria monocytogenes to intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 68%
“…A study performed on healthy weight mice found that there were significant changes in the gut microbiome as well as significant weight reduction in mice receiving either Lactobacillus rhamnosus GG or Lactobacillus sakei NR28 daily by oral gavage for 3 weeks. 82 There was no significant difference in food consumption between control and probiotic treatment groups, indicating that the significant reduction in epididymal fat mass was not due to a reduction of energy consumption. Results from this study indicate that the modulation of the gut microbiome with probiotic administration produces an anti-obesity effect that directly reduces epididymal fat mass.…”
Section: Application Of Probioticsmentioning
confidence: 87%
“…While this is an area of controversy due to the inconsistency in abundance of these two phyla in obese v. lean individuals, there is also variation between studies with respect to host species, samples evaluated (i.e. faecal v. intestine lumen v. intestinal mucosa), region of the gastrointestinal tract evaluated, and time point relative to obesity ( 37 , 38 ) . Nevertheless, these phyla continue to be associated with obesity in recent studies ( 39 , 40 ) and have not yet been evaluated relative to obesity in the horse.…”
mentioning
confidence: 99%